Discontinuation of Antihypertensive Medications on the Outcome of Hospitalized Patients With Severe Acute Respiratory Syndrome-Coronavirus 2. Issue 1 (July 2021) - Singh, Sandeep; Offringa-Hup, Annette K.; Logtenberg, Susan J.J.; Van der Linden, Paul D.; Janssen, Wilbert M.T.; Klein, Hubertina; Waanders, Femke; Simsek, Suat; de Jager, Cornelis P.C.; Smits, Paul; van der Feltz, Machteld; Jan Beumer, Gerrit; et al.
Abstract : RAASi (renin-angiotensin-aldosterone system inhibitors) are suggested as possible treatment option in the early phase of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection. A meta-analysis investigating the possible detrimental effects of RAASi on the severity of (SARS-CoV-2) infection showed that ambulatory use of RAASi, by hospitalized patients, has a neutral effect. It is, however, conceivable that this observation is biased by the fact that antihypertensive medications, are often discontinued at or during admission in hospitalized patients with SARS-CoV-2. We, therefore, investigated the effect of discontinuation of antihypertensive medications, in hospitalized patients with SARS-CoV-2. We performed a retrospective observational study on 1584 hospitalized patients with SARS-CoV-2 from 10 participating hospitals in the Netherlands. Differences in the outcome (severity of disease or death) between the groups in which medications were either continued or discontinued during the course of hospitalization were assessed using logistic regression models. Discontinuation of angiotensin receptor blockers, ACE (angiotensin-converting enzyme) inhibitors and β-blockers, even when corrected for sex, age, and severity of symptoms during admission, resulted in a 2 to 4× higher risk of dying from SARS-CoV-2 infection (odds ratio [95% CI]); angiotensin receptor blockers 2.65 [1.17–6.04], ACE inhibitor (2.28 [1.15–4.54]), and β-blocker (3.60 [1.10–10.27]). In conclusion, discontinuation of at-home ACE inhibitor, angiotensin receptor blockers, or β-blocker in patients hospitalized for a SARS-CoV-2 infection was associated with an increased risk of dying, whereas discontinuation of calcium channel blockers and diuretics was not. Abstract : Supplemental Digital Content is available in the text.